The Time-Course of Acute Changes in Corticospinal Excitability, Intra-Cortical Inhibition and Facilitation Following a Single-Session Heavy Strength Training of the Biceps Brachii - Latella, Christopher; Hendy, Ashlee M.; Pearce, Alan J.; VanderWesthuizen, Dan; Teo, Wei-Peng (Frontiers in Human Neuroscience, 2016)
Objective: The current understanding of acute neurophysiological responses to resistance training remain unclear. Therefore, we aimed to compare the time-course of acute corticospinal responses following a single-session heavy strength training (HST) of the biceps brachii (BB) muscle and provide quantifiable evidence based on the super-compensation model in an applied setting. Methods: Fourteen participants completed a counter-balanced, cross-over study that consisted of a single HST session (5 sets x 3 repetition maximum) of the BB and a control session (CON). Single- and paired-pulse transcranial magnetic stimulation (TMS) was used to measure changes in motor-evoked potential (MEP) amplitude, intra-cortical facilitation (ICF), short-interval intra-cortical inhibition (SICI) and long-interval intra-cortical inhibition (LICI). Additionally, maximal muscle compound wave (MMAX) and maximal voluntary isometric contraction (MVIC) of the BB were taken. All measures were taken at baseline, immediately post and at 10, 20, 30mins and 1, 2, 6, 24, 48 and 72hrs post-training. Results: A significant reduction in MEP amplitude was observed immediately post training (P = 0.001), while MVIC (P < 0.001) and MMAX (P = 0.047) were reduced for up to 30mins post-training. An increase in MVIC (p < 0.001) and MMAX (p = 0.047) was observed at 6hrs, while an increase in MEP amplitude (p = 0.014) was only observed at 48 and 72hrs. No changes in SICI, ICF and LICI were observed. Conclusion: Our results suggest that 1) acute changes in corticospinal measures returned to baseline in a shorter timeframe than the current super-compensation model (24-48hrs); and 2) changes in corticospinal excitability post-HST may be modulated “downstream” of the primary motor cortex.